Overlooked morphological variation and a proposal for a new taxonomic circumscription of Alyssum simplex (Brassicaceae) - Cetlová, Veronika; Fuertes-Aguilar, Javier; Iudova, Daria; Španiel, Stanislav (Phytotaxa, 2019)
A recent study of European annual taxa of Alyssum has revealed that A. simplex includes two cytotypes (diploid and tetraploid) which differ in genetic markers, evolutionary history, and monoploid relative genome size. In this paper we present a new taxonomic treatment of A. simplex in which we treat the two cytotypes as two separate species. We select and discuss suitable names for both taxa (diploid A. simplex and tetraploid A. collinum), examine their morphological differences and survey their geographic distribution. In addition, we compare both cytotypes with the morphologically similar and genetically related species A. strigosum and designate lectotypes and a neotype of several relevant names.